A Nutritional therapy in post laparatomy exploration and omental flap due to gastric perforation with nasoduodenal tube: a case report . - URFA; AS'AD, Suryani; MADJID, Mardiana; SAFITRI, Asrini (Nutrición Clínica y Dietética Hospitalaria, 2023)
Gastric perforation is a full thickness injury to the gastic wall. All forms of perforation in the gastrointestinal are surgical emergency cases. Perforation complications that occur in patients with gastric ulcers. The objective of this case study is to explain the support of nutritional therapy in patients with post laparotomy eksploration and omental flap due to gastic perforation with nasoduodenal tube. Case report ; A 71-year -old male patient with moderate malnutrition was admitted to an Ear Nose Throat ward. Physical examination reveals loss of subcutaneous fat,muscle wasting, nasogastic tube for the decompression and nasoduodenal tube for nutrient intake, there was postoperative wound on stomach. Blood test shows anemia ( 8,3 g/dl ), Leukocytosis (11.5 103/ul ), hypoalbuminemia (2,4 g/dl ), and moderate depletion immune system (1.173 103/ul). Nutrition therapy was given with a total calorie of 1800 kcal via nasoduodenal tube , protein 1.5-1,7 g/IBW/day, using low fiber blenderized food, a special Oral Nutrition Supplements ( hydrolized formula ). An addtional supplementation in the form of zinc, multivitamins, curcuma, and snakehead fish extract capsules. After 12 days of nutritional treatment, the patient was discharged with adequate oral nutrition. Postoperative wound healed. Improved blood test results such as hemoglobin (8,3 to 11,4 g/dl), leukocytes (11.5to 8.8 103/ul, the immune status (1.173 to 1.628 103/ul), albumin (2,4 to 3,2 g/dl). In conclusion, a special nutritional therapy improved nutritional status and clinical outcome in post laparotomy eksploration with omental flap due to gastric perforation patients